2020
DOI: 10.1186/s41927-020-0118-z
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs in ankylosing spondylitis patients receiving tumour necrosis factor inhibitor therapy; results from a large multinational real-world study

Abstract: Background: Symptoms and comorbidities of ankylosing spondylitis (AS) considerably reduce health-related quality of life (HRQoL) and ability to work. This real-world study assessed rates of tumour necrosis factor inhibitor (TNFi) use and switching, treatment failure, and associations between failing TNFi and HRQoL, work productivity and activity impairment (WPAI). Methods: AS patients and their treating physicians completed questionnaires capturing patient demographics, clinical status, TNFi treatment history,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…[20][21][22] A study of 223 consecutive patients with r-axSpA, which examined long-term drug survival of TNFi treatment over a 10-year period, revealed that female patients had significantly lower treatment survival rates than men (33.4 vs 44.9 months; p=0.031). 23 Differences in immunological markers between male and female patients with axSpA have been reported in the literature and may be responsible for different treatment responses to TNFi. One study showed that male patients with axSpA have significantly higher levels of TNF and IL-17A than female patients.…”
Section: Assessment Of Treatment Responsementioning
confidence: 99%
“…[20][21][22] A study of 223 consecutive patients with r-axSpA, which examined long-term drug survival of TNFi treatment over a 10-year period, revealed that female patients had significantly lower treatment survival rates than men (33.4 vs 44.9 months; p=0.031). 23 Differences in immunological markers between male and female patients with axSpA have been reported in the literature and may be responsible for different treatment responses to TNFi. One study showed that male patients with axSpA have significantly higher levels of TNF and IL-17A than female patients.…”
Section: Assessment Of Treatment Responsementioning
confidence: 99%
“…Finally, while not a primary aim of this study but because Australian data are lacking, we used these two datasets to estimate the population prevalence of AS. Based on the assumption that the 1925 AS patients that used a TNFi in 2020 represent 60% of all AS patients [16,17] in WA, the estimated point prevalence for AS was 0.29% in 2020. This figure agreed with the 0.28% period prevalence rate of AS amongst all hospital admissions in WA over 20 years (Suppl Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 Secukinumab has demonstrated significant long-term efficacy and safety versus placebo in patients with axSpA across various randomised clinical trials (RCTs). [6][7][8][9][10] RCTs evaluate sophisticated outcome measures including MRI, health-related quality of life with a stringent prospective, randomised and controlled design. 11 12 However, RCTs typically have a smaller and well-defined study population.…”
Section: How This Study Might Affect Research Practice or Policy?mentioning
confidence: 99%